Herbal Medicine Intervention for the Treatment of COVID-19: A Living Systematic Review and Cumulative Meta-Analysis - Ang, Lin; Song, Eunhye; Hu, Xiao-Yang; Lee, Hye Won; Chen, Yaolong; Lee, Myeong Soo (Frontiers in Pharmacology, 2022)
Background: Integrative herbal medicine has been reported to have beneficial effects in the treatment of coronavirus disease 2019 (COVID-19). Aim: To compile up-to-date evidence of the benefits and risks of herbal medicine for the treatment of COVID-19 symptoms. Methods: Eleven databases, including PubMed, Cochrane Register of Controlled Trials (CENTRAL), Embase, Allied and Complementary Medicine Database (AMED), Chinese National Knowledge Infrastructure Database (CNKI), Wanfang Database, and Chinese Science and Technique Journals Database (VIP), Research Information Service System (RISS), Korean Medical database (KMBase), Korean Association of Medical Journal database (KoreaMed), and OASIS database, were searched from 15 June, 2020, until March 28, 2022. Randomized controlled trials (RCTs), published in any language, reporting the efficacy and safety outcomes of herbal medicine in patients of all ages with a PCR-confirmed diagnosis of COVID-19 were included in this analysis. Data extraction and quality assessments were performed independently. Results: Random-effects meta-analyses showed evidence of favorable effects of treatment with herbal medicine when added to standard treatment, versus standard treatment alone, on the total effective rate (p=0.0001), time to remission from fever (p<0.00001), rate of remission from coughing (p<0.0001), fatigue (p=0.02), sputum production (p=0.004), improvement of manifestations observed on chest computed tomography scans (p<0.00001), incidence of progression to severe COVID-19 (p=0.003), all-cause mortality (p=0.003), time to a negative COVID-19 coronavirus test (p<0.0001), and duration of hospital stay (p=0.0003). There was no evidence of a difference between herbal medicine added to standard treatment, versus standard treatment alone, on the rate of remission from symptoms such as a fever, sore throat, nasal congestion and discharge, diarrhea, dry throat, chills, and the rate of conversion to a negative COVID-19 coronavirus test. Meta-analysis showed no evidence of a significant difference in adverse events between the 2 groups. There was an unclear risk of bias across the RCTs included in this analysis, indicating that most studies had methodological limitations. Conclusion: Current evidence suggests that herbal medicine added to standard treatment has potential benefits in the treatment of COVID-19 symptoms but the certainty of evidence was low. Registration: PROSPERO CRD42020191711.